CrossFit training impact on the level of special physical fitness of young athletes practicing judo - Osipov, A. Y.; Nagovitsyn, R. S.; Zekrin, F. H.; Fendel, T. V.; Zubkov, D. A.; Zhavner, T. V. (SportMont, 2019)
Experts indicate that one of the main factors for achieving significant success is athletes` physical (Podrigalo et al., 2019) and the functional fitness level in martial arts (Volodchenko, Podrigalo, Aghyppo, Romanenko, & Rovnaya, 2017). It is known that athletes` level of physical and functional fitness should be at their best when practising judo since judo is characterised by periodic high-intensity strength exercises (Mohammed & Choi, 2017). Moreover, experts also state that athletes need to develop muscle strength, strength and endurance to achieve significant competitive results (Franchini, Brito, Fukuda, & Artioli, 2014). Unfortunately, scientists have revealed a lack of physical fitness level among some elite Russian judoists (Adolf et al., 2018). Also, experts point out the lack of relevant data related to the possibility of a significant increase of judo athletes` physical and functional status (Ceylan, Gurses, Akgul, Baydil, & Franchini, 2018). It should be noted that it is customary to use hypoxic interval training to increase athletes` functional status in the practice of training elite fighters (Rovniy, Pasko, & Galimskyi, 2017). Russian experts point to the need to use exercises that affect the physical fitness of judo, thereby increasing athletes` level of endurance when practising judo. Surkov (2015) recommends using the following exercises: leap over partner while he is bent over and crawl under his legs after his partner stands up. Pashintsev and Surkov (2015) recommend the use of exercises with weights (30 seconds - exercise, 30 seconds - rest) for 5 minutes, followed by 5 minutes of rest.